Stigmatization and Interpersonal Deviance Behaviors of Tour Guides: The Influence of Self-Identity Threat and Moral Disengagement - Deng, Aimin; Liu, Wenxing; Long, Anna; Zhu, Yanghao; Gao, Kai (Frontiers in Psychology, 2022)
Severe tour guide stigma is a significant problem hindering tourism development. Based on self-identity threat and moral disengagement theory, this study analyzed the relationship between tour guide stigmatization and tour guides’ interpersonal deviance behavior. Survey data collected from 241 tour guides at three different points in time showed that tour guide stigmatization was positively related to tour guides’ interpersonal deviance behavior and that self-identity threat mediated this effect. The results also show that moral disengagement moderated the effect of tour guides’ self-identity threat on interpersonal deviance behavior, as well as the indirect effect of tour guide stigmatization on tour guides’ interpersonal deviance behavior via self-identity threat. This study enriches theoretical research on tour guide stigmatization and offers practical suggestions for solving stigmatization problems for tour guides and organizations.